Rational genomic optimization of DNA detection for human papillomavirus type 16 in head and neck squamous cell carcinoma. Issue 4 (18th December 2019) - Saito, Yuki; Favorov, Alexander V.; Forman, Michael; Ren, Shuling; Sakai, Akihiro; Fukusumi, Takahito; Liu, Chao; Sadat, Sayed; Ando, Mizuo; Xu, Guorong; Khan, Zubair; Pang, John; et al.
Abstract: Background: We aimed to use genomic data for optimizing polymerase chain reaction (PCR) primer/probe sets for detection of human papillomavirus (HPV)‐16 in body fluids of patients with HPV‐related head and neck squamous cell carcinoma (HPV‐HNSCC). Methods: We used genomic HPV‐HNSCC sequencing data from a single institutional and a TCGA cohort. Optimized primer/probe sets were designed and tested for analytical performance in CaSki HPV‐16 genome and confirmed in salivary rinse samples from patients with HPV‐HNSCC. Results: The highest read density was observed between E5 and L2 regions. The E1 region contained a region that was universally present. Among candidate PCR primer/probe sets created, six reliably detected 30 HPV‐16 copy number. In a CLIA certified laboratory setting, the combination of two novel primer/probe with E7 sets improved performance in salivary rinse samples with a sensitivity of 96% and specificity of 100%. Conclusions: PCR‐based detection of HPV‐16 DNA in HPV‐HNSCC can be improved using rational genomic design.